Evaluation of intradialytic hypoxemia development in intensive care patients - Uğur Uzun; Sibel Ersan; Işıl Köse Güldoğan; Aykut Sarıtaş; Nimet Şenoğlu (BMC Nephrology)
Abstract Introduction Hypoxemia is a significant factor contributing to increased mortality in intensive care patients and remains a prevalent issue. Although numerous conditions are well documented to lead to hypoxemia, intradialytic hypoxemia (IDH) occurring during dialysis is often overlooked. IDH is characterized by a decrease in arterial oxygen saturation below 90% or partial oxygen pressure (PaO₂) below 80 mmHg, and it may compromise tissue perfusion, adversely affecting patient prognosis. This study aims to enhance awareness of IDH in critically ill patients and to propose proactive strategies for the prevention of associated complications. Method The single-center observational study included 93 intensive care patients. Patients’ arterial and central venous blood gas values were measured before dialysis (baseline), at the third hour of dialysis (3rd hour), and one-hour post-dialysis (5th hour). The study evaluated PaO₂, partial pressure of carbon dioxide (PaCO₂), central venous oxygen saturation (ScvO₂), mean arterial pressure (MAP), perfusion index (PI) and the temperature gradient between the forearm and fingertip. Statistical analyses were conducted using the SPSS 26 software. Findings In patients who did not survive, a significant decrease was observed in PaO₂, ScvO₂, and perfusion index (PI) values at the third hour, while PaCO₂ levels and the central venous-to-arterial temperature gradient increased. No significant change was detected in mean arterial pressure (MAP) values. A partial trend toward improvement in these parameters was observed following dialysis. Survival rates among these patients were low, and survival duration was found to be short. Discussion and conclusion These changes indicate a deterioration in oxygen delivery and tissue perfusion. Therefore, close monitoring of these parameters during dialysis is of critical importance for the early identification of intradialytic hypotension (IDH) and the prevention of potential complications. Moreover, the observed low survival rates and short survival duration suggest that intradialytic pathophysiological changes may have a markedly adverse impact on patient prognosis. Clinical trial number Not applicable.